2020
DOI: 10.1093/beheco/araa100
|View full text |Cite
|
Sign up to set email alerts
|

Sensory ecology of the frog-eating bat, Trachops cirrhosus, from DNA metabarcoding and behavior

Abstract: Metabarcoding of prey DNA from fecal samples can be used to design behavioral experiments to study the foraging behavior and sensory ecology of predators. The frog-eating bat, Trachops cirrhosus, eavesdrops on the mating calls of its anuran prey. We captured wild T. cirrhosus and identified prey remains in the bats’ fecal samples using DNA metabarcoding of two gene regions (CO1 and 16S). Bats were preying on frogs previously unknown in their diet, such as species in the genus Pristimantis, which occurred in 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Douglas 1967, Vehrencamp et al 1977, Medellín 1988) are decades old and based on the identification of prey remains; there is a bias towards vertebrates, and arthropods are often reported only as orders. Recent studies using DNA barcoding (Ibáñez et al 2016, Arteaga Claramunt et al 2018, Jones et al 2020) have revealed new, taxonomically diverse prey with interesting ecological implications (Appendix ). While all the bat species have at least one account of predation of vertebrates, some species’ diets are much more reliant on them, so that vertebrates account for most taxa (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Douglas 1967, Vehrencamp et al 1977, Medellín 1988) are decades old and based on the identification of prey remains; there is a bias towards vertebrates, and arthropods are often reported only as orders. Recent studies using DNA barcoding (Ibáñez et al 2016, Arteaga Claramunt et al 2018, Jones et al 2020) have revealed new, taxonomically diverse prey with interesting ecological implications (Appendix ). While all the bat species have at least one account of predation of vertebrates, some species’ diets are much more reliant on them, so that vertebrates account for most taxa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Not enough data were found to include Mimon crenulatum, Nyctalus aviator, and Tonatia saurophila . Averages obtained from data by Ross (1961), Fleming et al (1972), O’Shea and Vaughan (1977), Vehrencamp et al (1977), Fenton et al (1981), Bell (1982), Schulz (1986), dos Reis and Peracchi (1987), Medellín (1988), Aldridge et al (1990), Fenton et al (1992), Martuscelli (1995), Fenton et al (2001), Bonato et al (2004), Ramanujam and Verzhutskii (2004), Lenhart et al (2010), Witt and Fabián (2010), Felix et al (2013), Kaliraj (2014), Ibáñez et al (2016), Barbosa Leal et al (2018), Czaplewski et al (2018), Jones et al (2020) and Carvalho et al (2020). Largest prey from data by Ruschi (1953), Prakash (1959), Vaughan (1976), Schulz (1986), Medellín (1988), Fenton et al (1990, 1992), Martuscelli (1995), Kalko et al (1996), Arias et al (1999), Ramanujam and Verzhutskii (2004), Thabah et al (2007), Ibáñez et al (2016), Czaplewski et al (2018) and Molina‐Moreira and Alava (2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While nocturnal activity may facilitate diurnal predator avoidance, it may also expose anoles to novel nocturnal predators. This could partially explain high anole predation by owls on Dominica [21] as well as predation by bats, besides their apparent ability to locate sleeping anoles [22]. From an invasive perspective, we note that the artificial night-light niche is utilized by many anole species with invasive populations [6,23,24].…”
mentioning
confidence: 99%